Netflix's Representation in the Case of 'Cyanide Coffee' in the film 'Ice Cold: Murder, Coffee, and Jessica Wongso: Critical Discourse Analysis Fairclough - Mutakhirani Mustafa; Nelly Husni Laely; Fransiska Densiana; Emi Anggreani; Eka Pitra (Hasanuddin University, 2024)
This research aims to describe the representation tendencies of Netflix in the documentary film